Focused Neuro-Otological Review of Superficial Siderosis of the Central Nervous System - Yoo, Aran; Jou, Jonathan; Klopfenstein, Jeffrey D.; Kattah, Jorge C. (Frontiers in Neurology, 2018)
Abstract Background: Infratentorial siderosis (iSS) is a progressive degenerative disorder targeting primarily the cerebellum and cranial nerve eighth; therefore, progressive ataxia and bilateral cochleovestibular loss are common. Toxicity from hemosiderin involves selectively vulnerable neurons and glia in these posterior fossa structures. Other neurologic findings may be present, though our focus relates to the cochlea-vestibular cerebellar involvement. Radiographic evidence of siderosis may be the result of recurrent, albeit covert bleeding in the subarachnoid (SA) space, or the consequence of an overt post-traumatic or aneurysmal subarachnoid hemorrhage SAH. The radiographic iSS appearance is identical regardless of the SAH cause. A recent study provides compelling evidence to search and correct possible hemorrhage sources in the spinal canal. The removal of residual existing hemosiderin deposits that may potentially cause clinical symptoms remains as a major therapeutic challenge Methods: We reviewed large data sources and identified salient papers that describe the pathogenesis, clinical and neurotologic manifestations and the radiographic features of iSS. Results: The epidemiology of iSS is unknown. In a recent series, clinically evident iSS was associated with recurrent SAH; in contrast, in a follow-up period ranging from weeks up to 11 years after a monophasic episode of SAH, radiographic siderosis was clinically silent. However, the post aneurysmal or post-trauma SAH sample size in this single study was small and their observation period relatively short; moreover, the burden of intraneuronal hemosiderin is likely greater with recurrent SAH. There are a few reports of late iSS, several decades after traumatic SAH. A recent report found subjective hearing loss in aneurysmal SAH individuals with radiographic siderosis. Only in recent years, it is safe to perform MRI in post-aneurysmal SAH, because of the introduction of Titanium, MRI-compatible aneurysm clips. Conclusion: iSS can be associated with significant neurotologic and cerebellar morbidity; the recurrent SAH variant is frequently clinically symptomatic, has a shorter latency and greater neurotologic disability. In these cases, a thorough search and management of a covert source of bleeding may stop clinical progression. The frequency and clinical course of radiographic iSS after traumatic and post-aneurysmal SAH is largely unknown. Detection of radiographic iSS after trauma or